Investigating the structural effect of achievement motivation and achievement on leadership and entrepreneurial spirit of students in higher education - Bambang Budi Wiyono; Hsin-Hung Wu (Administrative Sciences, 2022)
Today, it can be seen in the real world that many students are unemployed after graduating from college or university. Two soft skills are taught to determine the success of graduates at work, namely leadership and entrepreneurial spirit. The purpose of this study was to examine the structural effect of achievement motivation and achievement on student leadership and entrepreneurial spirit. This research was conducted in Indonesia, with a total sample of 789 students, through random sampling. Questionnaires and documentation techniques were used to collect the data, and then the data were analysed using descriptive statistics and structural equation modelling. The results showed that both exogenous variables, namely achievement motivation and achievement, affected both endogenous variables, but that achievement motivation had a stronger influence on student leadership and entrepreneurial spirit. In addition, the effect of achievement motivation was higher on entrepreneurial spirit than on leadership, whereas leadership influenced the entrepreneurial spirit of the students only to a small extent. The influences of these variables were then thoroughly discussed according to the theories and relevant research.
Keywords: 350; achievement; achievement motivation; entrepreneurial spirit; higher education; leadership; students